Micro-Inverter Control Strategies for Grid-connected PV Systems: A Comprehensive Review - Nyaupane, Madhusudan; Adhikari, Sujan; Tiwari, Shanti; Khanal, Asha (Journal of Science and Engineering, 2025)
This paper provides a comprehensive assessment of major micro-inverter configurations and control approaches used in photovoltaic (PV) systems, aiming to optimize power conversion efficiency, reduce total harmonic distortion (THD), and support reactive power regulation. It reviews several inverter structures, including push-pull, flyback, and dual buck-boost types, along with control strategies such as dq-axis transformation, Proportional-Resonant (PR) controllers, hysteresis modulation, and hybrid methods. Based on comparative research findings, THD levels vary between 2.46 % and approximately 7–8 %, while energy conversion efficiencies range from 88 % to over 93 %, depending on the specific system architecture and the Maximum Power Point Tracking (MPPT) technique implemented. The Quasi-Proportional Resonant (Q-PR) controller emerges as the most effective solution, offering superior dynamic response, excellent harmonic rejection, and robust performance under grid disturbances. Although many systems demonstrate accurate MPPT and fast transient behavior, they still face limitations related to scalability, reactive power capability, and adaptation to partial shading. The study concludes by emphasizing ongoing advancements in hybrid and sensorless control techniques as promising directions for developing economical and grid-compliant micro-inverter technologies for next-generation PV deployments.